Crowding out and imitation behavior in the solidarity game - Claudia Vogel; Jana Heimel; Friedel Bolle (European University Viadrina, Department of Business Administration and Economics, 2004)
In the Solidarity Game (Selten and Ockenfels, 1998), two "rich" persons can support a "poor" one. A strong positive correlation between one rich person's solidarity contribution and his expected contribution of the other is observed. This paper investigates the causality behind this correlation. Depending on the measure, we find that up to thirds of our subjects behave strategically. More than one third of the subjects show a crowding-out effect, i.e. they want to give less if they expect others to give more. This is no contradiction to the positive correlation if these subjects assume the others to be like themselves. In addition to strategic motives we find, for a quarter of the subjects, the wish to imitate their co-benefactors, usually however only for low contributions.
Keywords: D64; C72; C92; 330; Solidarity; Crowding out; Imitation; Solidarität; Spieltheorie; Altruismus; Crowding out; Konsuminterdependenz; Experiment; Theorie